Physicochemical evaluation of acid whey obtained from doble crema cheese produced in Belén, Boyacá, Colombia - Pineda, Erika; Torres-Vargas, Golda Meyer; Cepeda-Fonseca, Heley Estefany (Revista Colombiana de Investigaciones Agroindustriales, 2023)
The composition of acid whey makes it less usable, and it is an environmental and technical problem. This research aims to estimate the physicochemical characteristics of the doble crema cheese acid whey, from nine factories in the municipality of Belén in Boyacá. Laboratory methods were validated using the Lactoscan analyzer determinations and comparing them with reference methods. Accuracy was expressed in terms of relative error (% Edet) and f- and p-values; then, correlation curves were elaborated. To perform the physicochemical characterization of whey, fat, Solids-Not-Fat (SNF), protein, lactose, pH, total ash, calcium, density, and acidity were determined. The statistic of the comparison between analysis methods showed low percentages of relative error, there were no significant differences, and they had correlation coefficients greater than 0,8. The results of the physicochemical characterization showed differences in the content of protein, SNF, lactose, fat, ash, calcium, acidity, and pH. Each manufacturer has a manufacturing process for cheese and whey. There were no statistical differences for SNF, density, lactose, fat, ash, and pH within each company. However, there were differences between protein and acidity, even though companies work with the same quality of raw material and processing, there are deficiencies in the coagulation, drainage, and conservation of the whey. The analyzed acid whey is a good source of protein, calcium, lactose and has low fat content, which is attractive for manufacturing food products.